STRUCTURAL ABERRATIONS OF 1p36 IN HEMATOLOGIC MALIGNANCIES - Rahiye Dilhan Kuru; Ayşe Çırakoğlu; Şükriye Yılmaz; Şeniz Öngören; Muhlis Cem Ar; Teoman Soysal; Ayhan Deviren; Yelda Tarkan Argüden (İstanbul Tıp Fakültesi Dergisi)
Objective: Structural aberrations of 1p36 are very common in most hematologic malignancies. 1p36 consists of genes that are important in oncogenesis. The aim of this study was to define 1p36 abnormalities and their distributions within different hematologic malignancies.Materials and Methods: To achieve this goal, we retrospectively evaluated the cytogenetic results of our hematological cancer cases.Result: We found deletions or rearrangements of breakpoint 1p36 in 18 patients with various hematologic malignancies, including myelodysplastic syndrome (MDS), acute myeloid leukemia (AML), multiple myeloma (MM), chronic myeloid leukemia (CML), lymphoma, B cell acute lymphoblastic leukemia (B-ALL), idiopathic thrombocytopenic purpura (ITP) and aplastic anemia (AA). We observed t(1;3)(p36;p21) in one AML-M2 patient and t(1;3)(p36;q21) in two CML patients. Eight patients (1 MDS, 2 MM, 3 CML, 1 AML, and 1 AA) had translocations and rearrangements. One ITP patient had der(1)t(1;1)(p36;q21) and another CML patient had der(1)t(1;1)(p36;q12). We demonstrated several terminal deletions with different breakpoints between 1p11 and 1p36 in five patients, (2 MDS, 2 lymphomas, and 1 B cell acute lymphocytic leukemia).Conclusion: The 1p36 breakpoint is a hot spot for cancer-related chromosome rearrangements and is associated with poor prognosis. In order to emphasize the importance of 1p36 in hematologic malignancies it essential to build a large data pool on the subject. The distribution of breakpoints in 1p abnormalities in our series was remarkable, as 12 out of 18 1p breakpoints were 1p36. However, while 1p breakpoints aggregated on 1p36 in all translocations, there was only one 1p36 breakpoint in five deletions. With this paper, we contribute to the relevant literature by reporting our results.